Role of Maternal Obesity in Offspring Cardiovascular Development and Congenital Heart Defects - Ashleigh McMullan; James B. Zwierzynski; Nina Jain; Laura S. Haneline; Weinian Shou; Kok Lim Kua; Swetansu K. Hota; Matthew D. Durbin (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Congenital heart disease is a leading cause of death in newborns, yet many of its molecular mechanisms remain unknown. Both maternal obesity and diabetes increase the risk of congenital heart disease in offspring, with recent studies suggesting these conditions may have distinct teratogenic mechanisms. The global prevalence of obesity is rising, and while maternal obesity is a known risk factor for fetal congenital heart disease, the specific mechanisms are largely unexplored. Methods and Results We used a murine model of diet‐induced maternal obesity, without diabetes, to produce dams that were overweight but had normal blood glucose levels. Embryos were generated and their developing hearts analyzed. Transcriptome analysis was performed using single‐nucleus and bulk RNA sequencing. Global and phospho‐enriched proteome analysis was performed using tandem mass tag–mass spectroscopy. Immunobloting and histologic evaluation were also performed. Analysis revealed disrupted oxidative phosphorylation and reactive oxygen species formation, with reduced antioxidant capacity, evidenced by downregulation of genes Sod1 and Gp4x, and disrupted Hif1a signaling. Evidence of oxidative stress, cell death signaling, and alteration in Rho GTPase and actin cytoskeleton signaling was also observed. Genes involved in cardiac morphogenesis, including Hand2, were downregulated, and fewer mature cardiomyocytes were present. Histologic analysis confirmed increased cardiac defects in embryos exposed to maternal obesity. Conclusions These findings demonstrate that maternal obesity alone can result in cardiac defects through mechanisms similar to those associated with maternal hyperglycemia. This study provides valuable insight into the role of maternal obesity, a growing and modifiable risk factor, in the development of the most common birth defect, congenital heart disease.